2022
DOI: 10.3390/vaccines10040498
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Response in Hemodialysis Patients Following COVID-19 Vaccination and Breakthrough Infections during Delta and Omicron Variant Predominance

Abstract: Background: The advancement of COVID-19 vaccination programs globally has been viewed as an integral strategy to reduce both the number of COVID-19 cases and consequential complications of COVID-19, particularly for high-risk patient groups. There are limited data on the antibody response and protection from disease infection and severity in patients requiring hemodialysis (HD) following COVID-19 vaccination during the Delta and Omicron variant predominance. We conducted a study aiming to evaluate humoral immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…Now a new and even more infectious BA.2 variant is the most prevalent strain in Germany and worldwide. Our initial data on mild courses of infection in dialysis patients support most recent publications on 23 hemodialysis patients without any need for hospitalization [ 40 ] and give hope that the Omicron wave will not be associated with high hospitalization and mortality rates in this highly vulnerable patient group.…”
Section: Discussionsupporting
confidence: 77%
“…Now a new and even more infectious BA.2 variant is the most prevalent strain in Germany and worldwide. Our initial data on mild courses of infection in dialysis patients support most recent publications on 23 hemodialysis patients without any need for hospitalization [ 40 ] and give hope that the Omicron wave will not be associated with high hospitalization and mortality rates in this highly vulnerable patient group.…”
Section: Discussionsupporting
confidence: 77%
“…The development of merely mild symptoms in KTRs with breakthrough infections in our study cohort was in line with other studies that also documented only mild symptomatic breakthrough infections of patients postvaccination amid the predominant circulation of the Omicron versus the Delta variant. 46,47 Limitations of this study include the nonrandomized and monocentric design, the rather limited study size, and the heterogeneity of the cohort's vaccination regimes. Furthermore, the cellular response was only assessed 3 mo postvaccination, and no corresponding data were available for individuals before and 1 mo after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The development of merely mild symptoms in KTRs with breakthrough infections in our study cohort was in line with other studies that also documented only mild symptomatic breakthrough infections of patients postvaccination amid the predominant circulation of the Omicron versus the Delta variant. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…This was carried in nearly the same time as our study, and this can explain the similar incidence of breakthrough infections. The majority of this UK cohort also had had two doses of vaccinations, and only those with three doses had shown a better rate of protection [ 19 , 20 ]. Previous studies have shown that antibody titers can predict breakthrough infections [ 18 ].…”
Section: Discussionmentioning
confidence: 99%